EFEKTIVITAS PEMBELAJARAN BENTUK MOLEKUL DENGAN PEMODELAN REAL BERBASIS PENEMUAN TERBIMBING UNTUK MELATIHKAN KETERAMPILAN BERPIKIR TINGKAT TINGGI SISWA - Sutrisno Sutrisno; Sri Poedjiastoeti; I Gusti Made Sanjaya (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
This study aimed to describe the effectiveness of learning materials on shape of the molecule with the real modeling supported by PhET media-based on guided discovery to facilitate the students high-order-thinking skills at odd semester XI class of SMAN 10. This research is developmental research using 4D models. Thetest of the learning materials use one group pretest-posttest design. The results of validity syllabus (3.87), lesson plans (3.71), students book (3.35), work sheet (3.63), and test of products (3.58) are categorized very good and reliability syllabus (99%), lesson plans (100%), students book (89%), work sheet (100%), and test of products (100%) are categorized reliable. The Achievement test of higher-order thinking skills showed that the individuals completeness an average score of 82.79, the average sensitivity of items was 0.74 and the average individual gain score of 0.82. Students' response to the learning and teaching activities in average were well-categorized. Based on the findings of the study, it can be concluded that the shape of molecule with the real modeling supported by PhET media based on guided discoverywas effective to train the students' higher-order thinking skills.Penelitian ini bertujuan untukmendeskripsikan efektivitas perangkat pembelajaran bentuk molekul dengan pemodelan real ditunjang media PhET berbasis penemuan terbimbinguntuk melatihkan keterampilan berpikir tingkat tinggi siswa kelas XI semester ganjil SMAN 10 Samarinda pada materi bentuk molekul.Perangkat pembelajaran yang digunakan dikembangkan dengan model 4D. Perangkatpembelajaran di uji cobakan menggunakan one group pretest-posttest design. Validitas Silabus (3,87), RPP (3,71), BAS (3,35), LKS (3,63), dan LP Produk (3,58) berkategori sangat baik dan reliabilitas Silabus (99%), RPP (100%), BAS (89), LKS (100%), LP Produk (100%) berkategori reliabel. Tes hasil belajar keterampilan berpikir tingkat tinggi menunjukkan ketuntasan individual rata-rata 82,79, sensitivitas butir soal rata-rata 0,74 dan gain score individual rata-rata 0,82. Respon siswa terhadap perangkat pembelajaran dan kegiatan pembelajaran rata-rata baik.Berdasarkan temuan hasil penelitian dapat disimpulkan bahwa perangkat pembelajaran bentuk molekul dengan pemodelan real ditunjang media PhET berbasis model penemuan terbimbingefektif untuk melatihkan keterampilan berpikir tingkat tinggi siswa.